Rosemary and neem methanolic extract: antioxidant, cytotoxic, and larvicidal activities supported by chemical composition and molecular docking simulations - Alhaithloul, Haifa A. S.; Alqahtani, Mesfer M.; Abdein, Mohamed A.; Ahmed, Mohamed A. I.; Hesham, Abd El-Latif; Aljameeli, Mohammad M. E.; Al Mozini, Reem N.; Gharsan, Fatehia N.; Hussien, Suzan M.; El-Amier, Yasser A. (Frontiers in Plant Science, 2023)
The aim of this study was to employ GC-MS to assess the chemical composition of the MeOH leaves extract of R. officinalis and A. indica, and evaluate their insecticidal, antioxidant and antibacterial activities. Twelve components, representing 98.61% and 100% of the total volatile compounds, were deduced from the extracted R. officinalis and A. indica for each, respectively, using this method. In R. officinalis extract, limonene is typically positioned as the main component (23.03%), while the main chemicals identified in A. indica extract were methyl (E)-octadec-13-enoate (23.20%) and (2R)-1,3,8-trimethyl-4-propyl-5 ethyl-2-(1-hydroxyethyl)-7-methoxycardonylethyl-6-methylenecarbonyl-porphyrin (23.03%). Both extracts of R. officinalis and A. indica exhibited different degrees of toxicity against stored grain pests T. castaneum, with LC50 values of 1.470 and 2.588 mg/ml, respectively. Additionally, after 4 and 5hs of treatments at a concentration of 0.2 mg/ml, the A. indica extract showed the highest levels of repellent action (81.4% and 93.4%) and the R. officinalis extract showed a good repellent rate (64.9% and 80.7%) against T. castenum larva. With an IC50 value of 35.83 and 28.68 mg/L and a radical scavenging activity percentage of 67.76 and 72.35%, the leaves extract was found to be the most potent plant extract when tested for DPPH antioxidant activity. Overall results showed that MeOH extracts of R. officinalis and A. indica were more effective against S. aureus (18.90 and 17.21 mm, respectively) than E. coli (13.20 and 16.23 mm, respectively). In order to determine how the investigated chemicals, attach to the active sites of E. coli DNA gyrase A and S. aureus undecaprenyl diphosphate synthase, docking studies were carried out. The consensus score analysis showed that limonene exhibits the best binding energy with both enzymes in docking analysis, more stability in molecular dynamics simulations. The RMSD obtained from -7.8 and -3.4 (Kcal/mole). The two compounds were successfully used in a molecular dynamics simulation research to generate stable complexes with DNA Gyrase A